2014
DOI: 10.1177/0954410014550050
|View full text |Cite
|
Sign up to set email alerts
|

Shock loss model and blade profile optimization design of a supersonic cascade

Abstract: With the improvement of single-stage compressor load, the inflow velocity and relative Mach number at blade tip of compressor are further increased. Using supersonic blade profile to design highly loaded compressor is an effective method to satisfy the requirements of the compressor aerodynamic design. In the internal flow of a blade row, detached shock is caused at the leading edge of supersonic cascade, and complex passage shock structure is produced by shock and boundary layer interaction at blade surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, in these works, the second passage shock is simply modeled as an entire normal shock and the influences of shock-boundary layer interaction and back pressure on second passage shock strength and shape are not fully considered, which may result in significant disparity for shock loss prediction in the cases or operating conditions far away from the modeling case. Recently, a shock loss model has been developed by Sun et al 8 and applied to the optimization design of a transonic profile L030-6 resulting in 2% increment of total pressure recovery by reducing the terminal passage shock losses and shock-induced viscous losses. But in this model, the flow acceleration in cascade passage is neglected by considering the downstream Mach number of the first passage shock as the preshock Mach number of the terminal passage shock, which has discrepancy with the actual flow observed in experiments and reduces its usability in other cascades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these works, the second passage shock is simply modeled as an entire normal shock and the influences of shock-boundary layer interaction and back pressure on second passage shock strength and shape are not fully considered, which may result in significant disparity for shock loss prediction in the cases or operating conditions far away from the modeling case. Recently, a shock loss model has been developed by Sun et al 8 and applied to the optimization design of a transonic profile L030-6 resulting in 2% increment of total pressure recovery by reducing the terminal passage shock losses and shock-induced viscous losses. But in this model, the flow acceleration in cascade passage is neglected by considering the downstream Mach number of the first passage shock as the preshock Mach number of the terminal passage shock, which has discrepancy with the actual flow observed in experiments and reduces its usability in other cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a shock loss model has been developed by Sun et al. 8 and applied to the optimization design of a transonic profile L030-6 resulting in 2% increment of total pressure recovery by reducing the terminal passage shock losses and shock-induced viscous losses. But in this model, the flow acceleration in cascade passage is neglected by considering the downstream Mach number of the first passage shock as the pre-shock Mach number of the terminal passage shock, which has discrepancy with the actual flow observed in experiments and reduces its usability in other cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Their model was applied to two supersonic cascades, resulting in a significant reduction of 20% and 16% in the total pressure loss coefficient. Furthermore, Sun et al [22] conducted research to determine the primary source of shock losses. By developing a shock loss mechanism and validating the results, it was identified that the main source of loss in the supersonic cascade is the terminal passage shock loss.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], a multi-objective optimization of a 2D S-shaped supersonic profile, operating at a unique incidence condition, was conducted using a Kriging-assisted evolutionary algorithm in order to minimize total pressure losses and to maximize the pressure ratio. In [3,4], one-dimensional analytical shock-loss models were developed to predict overall total pressure losses. Upon these models, optimizations were conducted to reduce losses on two baseline geometries, acting on profile shape and thickness distribution.…”
Section: Introductionmentioning
confidence: 99%